AKTIVITAS ANTIRADIKAL BEBAS SERTA KADAR BETA KAROTEN PADA MADU RANDU (Ceiba pentandra) DAN MADU KELENGKENG (Nephelium longata L.) - I M. Oka Adi Parwata; K. Ratnayani; Ana Listya (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
It has been done the determination of free antiradical activity and beta caroten concentration on randu honey(Ceiba pentandra) and kelengkeng honey (Nephelium longata L.). The free antiradical activity determined bydiphenyl pykril hydrazil (DPPH) method according to sphectrophotometry UV-Vis, before that the honey was dilutedwith methanol and then the absorbance was measured on 497nm, 517 nm, and 537 nm. The beta karotenconcentration determination was done TLC-Sphetrophotodensitometrically by using beta caroten standard; the honeywhich was resulted by methanol maseration was partiated with acetone p.a. The next step was done by TLC withethyl acetate as an eluent : chloroform (3:7) and the peak of the analyt was read on TLC scanner 3.The result showed that the free antiradical activity on kelengkeng honey was greater than randu honey.Whereas the beta caroten concentration on kelengkeng honey was fewer than beta caroten concentration randuhoney. The activity of free antiradical and beta caroten concentration was 82,10 % and 1,9687 mg/100 g respectively,whereas for randu honey was 69,37 % and 3,6327 mg/100 g respectively.